Development of a Novel Sensor System Based on Magnetic Microspheres to Detect Cardiac Troponin T - Junrong Zhang; Hongxiang Liu; Baofeng Xu; Sijun Huang; Rui Liu; Jinming Zhu; Yi Guo; Li Xu (International Journal of Polymer Science)
Acute myocardial infarction (AMI) causes irreversible injury to cardiomyocytes in a short time and may result in various complications, severely threatening patient safety. Therefore, it is necessary to predict the possibility of AMI in the prophase. Prognostic detection of biomarkers that specifically reflect myocardial damage in a patient’s blood has become an essential mediating measure to prevent the serious occurrence of AMI. The present study is aimed at exploring a novel sensing system with high specificity and precision based on magnetic microspheres developed to detect cardiac troponin T (cTnT), which is the most specific diagnostic marker for AMI in cardiovascular diseases. Naive human cTnT protein in serum samples and antigens on functional magnetic microspheres will competitively bind with limited specific antibodies. After rapid removal of heterogeneous elements in the sera using a magnetic separator, fluorescein isothiocyanate-labeled immunoglobulin G is added to react with specific antibodies on the magnetic microspheres. Then, a flow cytometer is used to collect signals of different fluorescence intensities. The results show that the method is characterized by economy, high accuracy, and novelty. It can be used for the detection of cTnT in blood at 1.7–106.1 ng/mL, with a detection limit of 0.5 ng/mL. Thus, the proposed sensor improves the accuracy and efficiency of diagnosis before clinical deterioration of AMI.